Visualization and analysis of the antiquarian record in archaeology - Keen, D; Rahtz, S; Ucko, P (John Rylands University Library, 1992)
Computers are involved in many stages of an archaeologist's work, from field recording and data storage, to the analysis and presentation of information. This is not to suggest that all archaeologists use such technology, and that those who do use the computer for all processes from recording to presentation. Much of the software which is used in archaeology is not specifically written for the task to which it is applied, but is deemed applicable to the problems which archaeology presents. One consequence of this situation is that the applications of some specific computer methods are limited to those areas of archaeology which fit the criteria for pre-existing software. This paper deals with the problems of the analysis of antiquarian records (specifically dealing with the example of the records relating to the neolithic henge monument of Avebury) and the specification of software required to facilitate analysis. Such a solution involves the use of a computer for storage, analysis and presentation. The appeal of the computer is that it can mediate between these activities. We do not attempt in this paper either to cover the results of re-analysis of a site like Avebury, or to describe in detail the tools which either exist or need to be created; rather, we outline some of the existing tools and their uses, and prescribe in broad terms what the next generation of archaeologists will need. Although the majority of field archaeologists do not use antiquarian records, there will be an increasing need for tools which allow for analytical comparison of different interpretations of archaeological sites.